Perception of Entrepreneurship and Entrepreneurship Education Among Malaysian MBA Students : A Qualitative Study - Nasirdinov, Samat; Abdullah, Nor Mawarniwati (2013)
Entrepreneurship has gained significant interest in the new era of globalization. In order to move towards a knowledge-based economy, Malaysia has identified entrepreneurship as one of the key elements to strive the country‟s vision. Malaysia has begun to introduce various initiatives to stimulate entrepreneurial activity through promotions, trainings, funding and grants with the aim to provide an effective ecosystems that encourage and support the creation of innovative new venture. Thus, this study attempts to explore the perception of entrepreneurship and entrepreneurship education among Malaysian MBA students. A qualitative approach was used to investigate this topic. The findings show that improvements need to be addressed in the area of Government initiatives and entrepreneurship education to stimulate the birth of entrepreneurs. With the improvement, Malaysia would be well equipped in achieving the goal of being a developed country by Year 2020.